Factors Effecting Paddy Productivity in the MADA Regions, Malaysia - Kalimuthu, Kirttana; Applanaidu, Shri Dewi (UUM PRESS, 2024)
Rice commodity is becoming increasingly important for most countries worldwide, particularly those where rice is the main staple meal. This study examines the socioeconomic attributes of farmers, their perspectives on management practises, and the implementation of paddy machinery technology in the four MADA (Muda Agricultural Development Authority) regions in Malaysia. The study aims to determine the main factors effecting paddy productivity in the MADA regions. Primary data was collected from paddy farmers in the four MADA zones using a standardised questionnaire. The data was collected from 673 respondents from four regions of MADA. The analysis employed both descriptive statistics and regression analysis. The results indicate that variables such as land area, selection of paddy planting as the primary occupation, increased time spent on paddy farms, gender, and the educational background of farmers have a significant impact on paddy productivity in the MADA regions. The findings also show that, only a small percentage of respondents (6.2%) followed the crop schedule, and 93.8 percent of them were late. The utilisation of machinery in paddy cultivation achieved the following results: nine farmers achieved a success rate of 85.71 percent, while a majority of farmers (662 farmers) achieved a 71.43 percent utilisation rate, with one farmer earning the lowest usage rate of 57.14 percent. In conclusions the study has found that it is imperative to promote the use of management practises and advanced machinery technologies among paddy farmers to effectively increase productivity